STUDENTS THE ART OF TRADITIONAL SINGING PEDAGOGICAL CONTENT OF TEACHING - Mukhammatova Ozoda Muzrabovna (Western European Studies, 2025)
By studying the works of traditional singing, which are examples of the richest musical heritage of the Uzbek people, and analyzing their unique ideological and artistic content, it is possible to achieve that they glorify the ideas of the Motherland, nature, honesty, hard work, love for mother nature and people, peace, justice, and mobilization for the prosperity of the Motherland. This requires an important responsibility from future music teachers in the field of music education of higher pedagogical education and from the professors who have been teaching them. In this sense, this article serves to highlight that influencing the education of youth through the direction of traditional singing is an effective way to preserve and convey to young people a rich cultural heritage
Keywords: musical heritage; traditional singing; human qualities